2005
DOI: 10.1063/1.1833352
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations, potential representation and vibrational dynamics of He2Br2 van der Waals complex

Abstract: An intermolecular potential energy surface for He 2 Br 2 complex in the ground state is calculated at the levels of fourth-order ͑MP4͒ Møller-Plesset and coupled-cluster ͓CCSD͑T͔͒ approximations, using large-core pseudopotential for Br atoms and the aug-cc-pV5Z basis set for He. The surface is characterized by three minima and the minimum energy pathways through them. The global minimum corresponds to a linear He-Br 2 -He configuration, while the two other ones to ''police-nightstick'' and tetrahedral structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 59 publications
3
50
1
Order By: Relevance
“…Reported ab initio results have been shown that for He 2 Br 2 system, the pairwise atom-atom interactions are not able to describe the PES of the complex, while a sum of threebody HeBr 2 terms, 29 plus the He-He interaction, can accurately represent the interaction energies for this cluster. 34 This latter has been also supported by recent experimental data a) Electronic mail: alvaro.v@iff.csic.es.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Reported ab initio results have been shown that for He 2 Br 2 system, the pairwise atom-atom interactions are not able to describe the PES of the complex, while a sum of threebody HeBr 2 terms, 29 plus the He-He interaction, can accurately represent the interaction energies for this cluster. 34 This latter has been also supported by recent experimental data a) Electronic mail: alvaro.v@iff.csic.es.…”
Section: Introductionsupporting
confidence: 63%
“…These findings have been found to be in accord with predictions made by previous theoretical investigations for the tetraatomic clusters. 31,34 The work presented here expands our previous efforts to evaluate the multidimensional surfaces of such vdW complexes obtained from first principles ab initio computations, by direct comparison with the experiment. In this way we can study the role of uncertainties in the PES on the spectroscopic and dynamic properties of these systems.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Recent studies on the structure of He 2 Br 2 and HeICl complexes 50,51 and EQM calculations on He 2 Cl 2 24 have shown that the global PES for these systems is accurately approximated by…”
Section: B Potential Energy Surfacesmentioning
confidence: 99%